3 'Too much of a coincidence?' – identical twins with exertional heatstroke. (13th October 2015) - Smith, R; Ebbs, J; Jones, N; Martin, D; Kipps, C
Abstract : This report discusses a unique case of monozygotic twins that collapsed with Exertional Heat Stroke (EHS) during the same marathon in cool conditions. The twins were official race pacers in a city marathon held in the UK in early spring. Both recovered without complications due to the prompt recognition of EHS and use of aggressive cooling measures. This case illustrates that EHS is a complex illness with a genetic predisposition. The twins' role as race pacers was significant. They were unable to curtail their work rate and subsequently overrode their protective central governor mechanism. Runners should be aware of the risk of developing EHS and how to prevent it. We recommend medical teams should be prepared for EHS regardless of the environmental conditions and race distance.